IgA nephropathy: the lectin pathway and implications for targeted therapy - Barratt, Jonathan; Lafayette, Richard A; Zhang, Hong; Tesar, Vladimir; Rovin, Brad H; Tumlin, James A; Reich, Heather N; Floege, Jürgen (Kidney international, 2023)
Many patients with immunoglobulin A nephropathy (IgAN) progress to kidney failure even with optimal supportive care. An improved understanding of the pathophysiology of IgAN in recent years has led to the investigation of targeted therapies with acceptable tolerability that may address the underlying causes of IgAN or the pathogenesis of kidney injury. The complement system-particularly the lectin and alternative pathways of complement-has emerged as a key mediator of kidney injury in IgAN and a possible target for investigational therapy. This review will focus on the lectin pathway. The examination of kidney biopsies has consistently shown glomerular deposition of mannan-binding lectin (1 of 6 pattern-recognition molecules that activate the lectin pathway) together with IgA1 in up to 50% of patients with IgAN. Glomerular deposition of pattern-recognition molecules for the lectin pathway is associated with more severe glomerular damage and more severe proteinuria and hematuria. Emerging research suggests that the lectin pathway may also contribute to tubulointerstitial fibrosis in IgAN and that collectin-11 is a key mediator of this association. This review summarizes the growing scientific and clinical evidence supporting the role of the lectin pathway in IgAN and examines the possible therapeutic role of lectin pathway inhibition for these patients.
Keywords: lektiny; glomerulus; imunoglobulin A; Kidney Glomerulus; Kidney; lidé; Immunoglobulin A; IgA nephropathy; Lectins; IgA nefropatie; ledviny; glomerulonephritis; Humans; complement; Glomerulonephritis, IGA